A software product line experience - Andriano, Natalia Valeria (2005)
Previous work in software product lines showed an increment of up to 10 times in productivity and product quality [SEI Prod_Line]; because of this, the software product line approach is critical for the success of a development project including a common platform. There are several differences between the traditional development techniques and the software product line approach. This initiative differs in scope and approach that is the reason why new areas of study were created, namely Domain Engineering and Software Product Line Architecture. For the development of a software platform in GSG Argentina we took the software product line approach and combined different known practices of Domain Engineering and Software Architecture in order to adapt them to our project's context. This paper describes lessons learned during the development of this project, such as the tailorization of the application of FORM (Feature-Oriented Reuse Method), the use of existing standards and cases of study to extract and infer knowledge of the problem domain, how we interact with marketing and system engineering areas in order to gather relevant functional and quality features of the platform, documentation practices, challenges we found and the approaches we took to solve them